Impact of changing provider remuneration on NHS general dental practitioner services in Northern Ireland: a mixed-methods study - Paul Brocklehurst; Martin Tickle; Stephen Birch; Ruth McDonald; Tanya Walsh; Tom Lloyd Goodwin; Harry Hill; Elizabeth Howarth; Michael Donaldson; Donncha O'Carolan; Sandy Fitzpatrick; Gillian McCrory; et al. (National Institute for Health Research, 2020)
Background: Policy-makers wanted to reform the NHS dental contract in Northern Ireland to contain costs, secure access and incentivise prevention and quality. A pilot project was undertaken to remunerate general dental practitioners using a capitation-based payment system rather than the existing fee-for-service system. Objective: To investigate the impact of this change in remuneration. Design: Mixed-methods design using a difference-in-difference evaluation of clinical activity levels, a questionnaire of patient-rated outcomes and qualitative assessment of general dental practitioners' and patients' views. Setting: NHS dental practices in Northern Ireland. Participants: General dental practitioners and patients in 11 intervention practices and 18 control practices. Interventions: Change from fee for service to a capitation-based system for 1 year and then reversion back to fee for service. Main outcome measures: Access to care, activity levels, service mix and financial impact, and patient-rated outcomes of care. Results: The difference-in-difference analyses showed significant and rapid changes in the patterns of care provided by general dental practitioners to patients (compared with the control practices) when they moved from a fee-for-service system to a capitation-based remuneration system. The number of registered patients in the intervention practices compared with the control practices showed a small but statistically significant increase during the capitation period (p < 0.01), but this difference was small. There were statistically significant reductions in the volume of activity across all treatments in the intervention practices during the capitation period, compared with the control practices. This produced a concomitant reduction in patient charge revenue of £2403 per practice per month (p < 0.05). All outcome measures rapidly returned to baseline levels following reversion from the capitation-based system back to a fee-for-service system. The analysis of the questionnaires suggests that patients did not appear to notice very much change. Qualitative interviews showed variation in general dental practitioners' behaviour in response to the intervention and how they managed the tension between professional ethics and maximising the profits of their business. Behaviours were also heavily influenced by local context. Practice principals preferred the capitation model as it freed up time and provided opportunities for private work, whereas capitation payments were seen by some principals as a 'retainer fee' for continuing to provide NHS care. Non-equity-owning associates perceived the capitation model as a financial risk. Limitations: The active NHS pilot period was only 1 year, which may have limited the scope for meaningful change. The number of sites was restricted by the financial budget for the NHS pilot. Conclusions: General dental practitioners respond rapidly and consistently to changes in remuneration, but differences were found in the extent of this change by practice and provider type. A move from a fee-for-service system to a capitation-based system had little impact on access but produced large reductions in clinical activity and patient charge income. Patients noticed little difference in the service that they received. Future work: With changing population need and increasing financial pressure on the NHS, research is required on how to most efficiently meet the expectations of patients within an affordable cost envelope. Work is also needed to identify and evaluate interventions that can complement changes in remuneration to meet policy goals. Trial registration: Current Controlled Trials ISRCTN29840057. Funding: This project was funded by the National Institute for Health Research (NIHR) Health Services and Delivery Research programme and will be published in full in Health Services and Delivery Research; Vol. 8, No. 6. See the NIHR Journals Library website for further project information.